WALKER – A self-care tool for creative introspection - Spors, Alexa Velvet (2017)
Current mental health applications tend to translate traditional approaches into the digital space – without fully tapping into the potential of the devices they are being run on. As practise-led research, this study examines the feasibility of creating a playful and creative mental health application that recognises this potential. Informed by an exploration of power in therapeutic technology and participatory design principles, WALKER is a user-generated collaborative artwork and tool for self-care that operates outside the clinical paradigm of “mental illness”.